STRATEGI RUMAH TANGGA NELAYAN DALAM MENGATASI KEMISKINAN (STUDI DI KEPENGHULUAN PANIPAHAN DARAT KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR PROVINSI RIAU) - Tirta Anugerah; Viktor Amrifo; Hendrik Hendrik (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This research was conducted on November 2015 to November 2015 in Kepenghuluan Panipahan Darat Kecamatan Pasir Limau Kapas Kabupaten Rokan Hilir Riau Province. The objective of this research was to analyze the factors that caused poverty in fishermen laborers and identify effors by the fishermen laborers in overcoming poverty. This reserch used the case study method to determine informants using snowball sampling technique. Informants were taken 20 households were recipients of Bantuan Langsung Tunai Masyarakat (BLSM) who pay attention to 12 years of education for their children. The datas were collected by interview and analyzed used avalitative descriptive by analizing the causes of poverty and identify the efforts made in overcoming poverty. Based on the result of this research, the causes of poverty household of fishermen caused by low income and high spending, low income impected by the low level of education, low diversification of jobs, and declining catches. While higher spending was infwenced by bad habits debt and consumer behaviour, the alienation residence, sanitation and clean water as well as the large number of family burden. The strategy to overcome poverty carried out with increase income and reduce costs. Increase income by diversifying the work, the role of household members, the utilization of social networking like debt and social gathering. While reduce costs by pressing expenditure meal and non meal.